Influence of preceding legumes, N levels and irrigation in rabi sorghum (Sorghum bicolor) - NAAIIK, RVT BALAZZII; MISHRA, J S; MADHAVI, A (The Indian Journal of Agricultural Sciences, 2019)
An experiment was conducted during post-rainy seasons of 2012–13 and 2013–14 at Indian Institute of Millet Research, Rajendranagar, Hyderabad to see the effect of preceding legumes, irrigation and N levels on rabi sorghum (Sorghum bicolor (L.) Moench) productivity and soil quality. Results revealed that the in situ incorporation of Sesbania during kharif significantly increased the grain yield (2511 and 3024 kg/ha) of post-rainy sorghum as compared to kharif fallow (2409 and 2930 kg/ha). Further, irrigation at four critical stages, viz. PI, booting, anthesis and milking had significantly out yielded other irrigation levels. Application of 60 kg N/ha produced grain yield on a par with 90 kg N/ha. Sesbania green manure incorporated plots contained significantly more population of soil microbes (bacteria, fungi and actinomycetes). The available nutrients (NPK) were significantly higher due to the incorporation of Sesbania as compared to the haulms of greengram or stubbles of cowpea.